Diagnostic value of subependymal pseudocysts and choroid plexus cysts on neonatal cerebral ultrasound: a meta-analysis. Issue 6 (25th March 2009) - Fernandez Alvarez, J R; Amess, P N; Gandhi, R S; Rabe, H
Abstract : Background and objective: Subependymal pseudocysts and choroid plexus cysts are seen in newborns on cerebral ultrasound. Clinicians are unsure whether these findings are related to an underlying disease which affects long-term outcome and requires medical intervention. In an attempt to establish the diagnostic value of cystic lesions on cerebral ultrasound and guide clinical management we searched the medical literature and performed a meta-analysis. Methods: We performed a systematic literature review and summarised the data on the value of subependymal pseudocysts or choroid plexus cysts for the diagnosis of chromosomal anomalies or congenital infections. Sensitivity, specificity, predictive values and likelihood ratios were calculated for single, multiple, unilateral and bilateral cysts. Results: 305 patients with cystic lesions were retrieved. Bilateral cysts, irrespective of their number, had a sensitivity of 88% and negative predictive value of 94% for a congenital infection or genetic disorder. Unilateral single cysts had a specificity of 92% for normal microbiological and genetic results. Bilateral multiple subependymal pseudocysts or choroid plexus cysts had a positive likelihood ratio of 9.1 for a chromosomal anomaly or congenital infection. Unilateral cysts had a negative likelihood ratio of 0.2 for a congenital infection or chromosomal anomaly. There was a chance of 1 in 4–5 for a congenital infection or chromosomal anomaly if bilateral multiple subependymal pseudocysts or choroid plexus cysts were found. Conclusions: Bilateral multiple subependymal pseudocysts or choroid plexus cysts suggest an underlying disease. Further investigations should be undertaken even if the patient is otherwise normal. Parents of well newborns with a single cyst should be reassured.